Pengertian Tafsir dan Coraknya dari Zaman Nabi Hingga Sekarang - Dinda Salsabilla; Hanifa Hanifa; Muhammad Aidil Dalimunthe; Jendri Jendri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Tafsir is a term originating from Arabic which means explanation or explanation. In the context of the Islamic religion, tafsir more specifically refers to the explanation of the Al-Qur'an. Scholars or interpreters seek to understand the meaning contained in the verses of the Qur'an, both literally and in deeper meaning, so that they can be applied in everyday life. Tafsir is a science that studies the Al-Qur'an, which is an in-depth science, where experts try to understand the Arabic language of the Al-Qur'an, the historical context of the revelation of the verses, as well as various other relevant aspects to gain a comprehensive understanding. The main goal of tafsir is to understand the meaning contained in the Qur'an. This includes understanding the meaning of words per word, the meaning of sentences, and the meaning of the entire verse or surah. Tafsir is also used to explore Islamic laws originating from the Al-Qur'an. Scholars use tafsir to understand commands, prohibitions, and various other legal provisions contained in the Koran. Tafsir helps Muslims to understand God's messages contained in the Koran, these messages cover various aspects of life, such as creed, worship, muamalah, and morals.